Transradial approach in vertebral artery stenting - Zhang, Yao; Lan, Wenya; Liu, Hui; Yuan, Kang; Ye, Ruidong (Frontiers in Neurology, 2025)
BackgroundThe transradial approach (TRA) has been gaining attraction for endovascular procedures. This study aimed to compare the efficacy and safety of the TRA vs. the transfemoral approach (TFA) for stenting in patients with vertebral artery (VA) stenosis.MethodsWe retrospectively enrolled consecutive patients treated with endovascular stenting in the V1 segment of the vertebral artery from August 2020 to October 2021. We divided patients into two groups (TRA group and TFA group) and compared the procedure outcomes, post-procedure complications, and long-term outcomes with logistic regression models and propensity score-matching methods.ResultsAmong the 109 enrolled patients, 45 patients were treated via TRA and 64 patients were treated via TFA. The TRA group had a significantly shorter procedure time (43 vs. 50 min, p = 0.005) and a shorter length of stay than the TFA group. The post-procedure complications were slightly higher in the TFA group than in the TRA group (10.9% vs. 2.2%, p = 0.179).ConclusionThis study found that TRA was a safe and feasible approach for vertebral artery stenting of V1 segment stenosis. TRA demonstrated advantages in reducing procedural time and length of stay compared to TFA. However, further large-scale and randomized controlled studies are warranted to verify these findings, given the retrospective and non-randomized nature of this study.